Multivalued backward stochastic differential equations with local lipschitz drift - N'zi, Modeste (Stochastics and stochastics reports, 1997)
We deal with a one dimensional multivalued backward stochastic differential equation associated to the subdifferential ∂hof a lower semi-continuous convex function h, with a local lipschitz coefficient (drift). When the terminal value is bounded, we prove the existence of a solution by using a suitable approximation of the drift by a double sequence of lipschitz functions. The uniqueness is obtained under the condition that the drift is local Lipschitz in y and globally Lipschitz in z. The existence result is an extension to the multivalued setting of the work of Hamadène